DETERMINAN YIELD OBLIGASI PEMERINTAH TENOR 5 TAHUN DENGAN MENGGUNAKAN MODEL EGARCH PADA NEGARA INDONESIA, MALAYSIA, THAILAND, DAN FILIPINA - Paramita, Rio Putri (Diponegoro Journal of Management, 2016)
This research aims to analyze the effect of interest rates, inflation, oil prices, exchange rates, and foreign exchange reserves on bond yields. This research was conducted on 5-year government bond from four member countries of ASEAN, that is Indonesia, Malaysia, Thailand, and Philippines during the period 2006 to 2015.The data used in this research is the monthly data of government bond yields, interest rates (policy rates), oil prices (West Texas Intermediate), exchange rates, and foreign exchange reserves. The data obtained from Bank of Indonesia website, Bank of Thailand website, and Bloomberg. The analysis method used for this research is Exponential Generalized AutoRegressive Conditional Heteroscedasticity (EGARCH). The data analysis phase through the data stationary test, EGARCH estimation, Akaike information criterion (AIC) and schwartz criterion (SC) test, ARCH LM test, and Z-statistic test.The results find that oil prices and exchange rates have positive and significant effect on government bond yields for all the countries studied, both Indonesia, Malaysia, Thailand, and Filipina. Interest rates have positive and significant effect on Indonesia and Thailand government bond yields. Inflation has positive and significant effect on Malaysia and Thailand government bond yields. While foreign exchange rates have negative and significant effect on Indonesia and Thailand government bond yields.